2000
DOI: 10.1557/mrs2000.152
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Transparent Conducting Oxides

Abstract: As the areas of the major applications of transparent conducting oxides (TCOs) increase, demand will grow for materials having lower sheet resistance while retaining good optical properties. Simply increasing the film thickness is not acceptable because this would increase the optical absorptance. New materials must be developed with lower resistivities than previously achieved and with optical properties superior to those of the present generation of TCOs. This has now been recognized internationally, and nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
215
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(223 citation statements)
references
References 10 publications
4
215
0
1
Order By: Relevance
“…, the Drude model can be generally used to represent the decrease in the transmittance [23][24][25]. Briefly, the model indicates that the transmittance drop in the near infrared region is associated with the plasma frequency (ω p ) that can be expressed as follows:…”
Section: Methodsmentioning
confidence: 99%
“…, the Drude model can be generally used to represent the decrease in the transmittance [23][24][25]. Briefly, the model indicates that the transmittance drop in the near infrared region is associated with the plasma frequency (ω p ) that can be expressed as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Among possible routes to avoid compromising the optical transparency [4,5] is to enhance conductivity via mobility of the free carriers rather than their concentration. Recently, the mobility with more than twice the value of the typical commercial TCO materials such as Sn-doped indium oxide (ITO) was observed in Mo-doped In 2 O 3 (IMO), and it was shown that the conductivity can be significantly increased with no changes in the spectral transmittance upon doping with Mo [6,7,8,9].…”
mentioning
confidence: 99%
“…It has many advantageous properties such as low resistivity, high transparency in the visible light wavelength, and long-term stability [2]. Several methods have been employed successfully to deposit ITO films.…”
Section: Introductionmentioning
confidence: 99%